Fungsi Modal Sosial dalam Meningkatkan Kesejahteraan Ekonomi : (Studi pada Perempuan Pengolah Ikan Asin di Kota Bangun) - Amelia, Safitri; Riyadi, Riyo; Reza, Reza (Faculty of Teacher Training and Education, Mulawarman University, 2024)
The research aims to determine the role of social capital in improving the economic welfare of women processing salted fish in Bangun City. This research is descriptive research with a qualitative approach. Data collection uses interviews and observations. The informants in this study consisted of 10 people, namely, 1 person who owns a salted fish processing business, 2 fishermen who sell the fish they get and 7 women who process salted fish in Bangun City. The results of this research show that women's involvement in salted fish processing activities and the economic impact obtained from their collaboration. Women who process salted fish carry out this work to help improve the economic welfare of their families so that women who process salted fish fill their free time by working as fish processors. Satly. Social capital in the group of women processing salted fish is trust, formed from daily behavior in always being honest and not committing fraud, having social norms in the form of etiquette or polite behavior in daily life and a social network between women processing fish. salted fish with family ties between women processing salted fish, friendships and the community environment.